2016
DOI: 10.15171/jrip.2017.37
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of contrast-induced nephropathy a prospective study

Abstract: Introduction: Contrast-induced acute kidney injury (AKI) is one of the most common causes of hospital-acquired AKI. Objectives: To determine the incidence of contrast induced nephropathy (CIN), to identify significant risk factors associated with CIN and to compare the variations in serum creatinine levels with and without contrast exposure. Patients and Methods: A total of 222 patients (124 males and 98 females with mean age of 48.96 ± 16.74 years) who received iodinated contrast agents during different proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 27 publications
0
9
0
6
Order By: Relevance
“…This might be due to variable criteria and definitions of PC-AKI among the studies as well as different study designs. In Europe and the US, the incidence of PC-AKI after CTA or CTP reportedly ranges from 1.5% to 14.8% [7][8][9][10][11][12]. The risk of PC-AKI may be elevated in patients with older age, longterm and uncontrolled diabetes, renal insufficiency, and concurrent use of nephrotoxic drugs [13].…”
Section: Introductionmentioning
confidence: 99%
“…This might be due to variable criteria and definitions of PC-AKI among the studies as well as different study designs. In Europe and the US, the incidence of PC-AKI after CTA or CTP reportedly ranges from 1.5% to 14.8% [7][8][9][10][11][12]. The risk of PC-AKI may be elevated in patients with older age, longterm and uncontrolled diabetes, renal insufficiency, and concurrent use of nephrotoxic drugs [13].…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Shlaja et al, the average age of patients was 35.75 years. In the study conducted byPeer et al (2017) on 222 patients, the proportion of male subjects was higher than the female (men 55.8% vs women 44.2%), and the average age of patients in this study was 48.96 years. The study by Marenzi et al (2009) also found a NGAL has been studied as a potential biomarker to foretell renal injury before any functional abnormalities were observed.…”
mentioning
confidence: 53%
“…The authors of those studies concluded that intravenous contrast administration is not a risk factor for AKI, even in patients with impaired renal function or with comorbidities that can predispose to nephrotoxicity ( 1 , 15 - 17 ) . Nevertheless, other authors have concluded that intravenous contrast administration is a risk factor for AKI in patients with CKD and diabetes mellitus ( 7 , 9 , 10 , 18 ) .…”
Section: Discussionmentioning
confidence: 97%
“…With an average incidence of 11%, CIN is recognized as the third leading cause of AKI in hospitalized patients ( 6 ) . However, the reported incidence ranges from 1% and 50%, depending on the characteristics of the population studied and whether intra-arterial or intravenous contrast is used ( 7 - 10 ) . Among patients receiving intravenous contrast alone, the reported incidence of CIN can vary from 2.5% to 12% ( 7 - 10 ) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation